Environmental and genetic risk factors for MS: an integrated review. Issue 9 (7th August 2019) - Waubant, Emmanuelle; Lucas, Robyn; Mowry, Ellen; Graves, Jennifer; Olsson, Tomas; Alfredsson, Lars; Langer‐Gould, Annette
Abstract: Recent findings have provided a molecular basis for the combined contributions of multifaceted risk factors for the onset of multiple sclerosis (MS). MS appears to start as a chronic dysregulation of immune homeostasis resulting from complex interactions between genetic predispositions, infectious exposures, and factors that lead to pro‐inflammatory states, including smoking, obesity, and low sun exposure. This is supported by the discovery of gene–environment (GxE) interactions and epigenetic alterations triggered by environmental exposures in individuals with particular genetic make‐ups. It is notable that several of these pro‐inflammatory factors have not emerged as strong prognostic indicators. Biological processes at play during the relapsing phase of the disease may result from initial inflammatory‐mediated injury, while risk factors for the later phase of MS, which is weighted toward neurodegeneration, are not yet well defined. This integrated review of current evidence guides recommendations for clinical practice and highlights research gaps.